If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1y = 1 + y Solving 1y = 1 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 1y + -1y = 1 + y + -1y Combine like terms: 1y + -1y = 0 0 = 1 + y + -1y Combine like terms: y + -1y = 0 0 = 1 + 0 0 = 1 Simplifying 0 = 1 Combine like terms: 0 + -1 = -1 -1 = 1 + -1 Combine like terms: 1 + -1 = 0 -1 = 0 The solution to this equation could not be determined.
| (x^3-3x+2x^2-5)=0 | | 47-3x=6x+21 | | 5x+2=-x | | 7(3x+4)-1=-78 | | 7x+42=x+12 | | 4x^2=9+41 | | 7e^4x-5=11 | | 7x+3x=44 | | -x+x-2=2 | | 10x+45=x+81 | | 7x+3x=72 | | 12-(n-3)= | | 7=2x+11 | | R+4=20 | | z+4.9=8.8 | | 7x+60=x-6 | | 45=-5(k+4) | | 2/5x-=1/5x-12 | | 2sin^2-3cos+1=0 | | 11a^2+2a-17=0 | | 5a+6a=-6+8a | | 360=(x+40)+(4x+70)+(2x+110) | | x+47=54 | | 4x^2-2-8w=-6x | | -14x+1=21 | | 360=(x+50)+(2x+80)+(4x+20) | | x^4-5x^3-2x^2-3x-9= | | 5y-(3y+8)=3-(7y-9) | | 5(x-1)=3(2-x)-5 | | x+52=61 | | 11v-2v=54 | | x+78=86 |